2018
DOI: 10.1177/2325967118804204
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of 3 Syndesmosis Repair Techniques With Suture Button Implants

Abstract: Background:Suture button fixation of syndesmotic injury is growing in popularity, as it has been shown to provide adequate stability in a more cost-effective manner than screw fixation while allowing more physiologic distal tibiofibular joint motion. However, the optimal repair technique and implant orientation have yet to be determined.Purpose/Hypothesis:The purpose of this study was to biomechanically compare 3 suture button construct configurations/orientations for syndesmosis fixation: single, parallel, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 29 publications
0
26
0
3
Order By: Relevance
“…This study does not take into account the effect of cyclic loading, which may provide insight into the durability of the constructs, but previous biomechanical studies have shown that there may not be significant differences between fixation methods with increasing cyclic loading. 17 The findings from this study will serve as a foundation to support in vivo kinematic testing to further evaluate which fixation technique is best for early weightbearing after syndesmotic injury.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This study does not take into account the effect of cyclic loading, which may provide insight into the durability of the constructs, but previous biomechanical studies have shown that there may not be significant differences between fixation methods with increasing cyclic loading. 17 The findings from this study will serve as a foundation to support in vivo kinematic testing to further evaluate which fixation technique is best for early weightbearing after syndesmotic injury.…”
Section: Discussionmentioning
confidence: 86%
“…1,26 Suture button fixation has potential advantages over screw fixation, such as allowing for physiological tibiofibular motion while maintaining reduction, decreasing the need for implant removal, and allowing earlier rehabilitation. 17 Further, divergent suture button fixation has the theoretical advantage of controlling tibiofibular motion in 2 planes, especially in the sagittal plane, which has been an issue with single suture button constructs in some previous biomechanical studies. 2 Regardless of which fixation method is used, anatomic reduction of the syndesmosis is critical in order to achieve good functional outcomes after surgery.…”
mentioning
confidence: 99%
“…Trabajos realizados en los últimos años que analizan los resultados de métodos de fijación dinámica frente a los tradicionales tornillos transindesmales reflejan leve superioridad con menor porcentaje de casos de mala reducción posquirúrgica. Asimismo, la tasa de reintervención y de pérdida de reducción es menor en el grupo de fijación dinámica, especialmente si el en grupo de pacientes sometidos a fijación con tornillo transindesmal se procede a la retirada sistemática del mismo (Tabla 2) (41)(42)(43)(44)(45)(46) .…”
Section: Casos Clínicos 2002unclassified
“…En relación con la fijación dinámica, recientes estudios biomecánicos en cadáver que analizan diferentes opciones técnicas en cuanto al número y la disposición de los implantes no han evidenciado diferencias significativas, por lo que la colocación de un segundo dispositivo sería electiva y, aunque proporcionaría mayor seguridad en cuanto a la fiabilidad de la fijación ante la eventual pérdida de uno de ellos, podría obviarse en aquellos casos en los que las lesiones asociadas en peroné distal dificulten la colocación de un segundo implante (46) .…”
Section: Casos Clínicos 2002unclassified
“…Si bien los tornillos siempre demostraron ser superiores en estudios biomecánicos, ya contamos con diversos trabajos que han demostrado que el sistema TightRope® es comparable a un tornillo tricortical de 3,5 mm (7) . Respecto a la configuración, un reciente estudio en cadáver compara la fijación dinámica simple, la doble paralela y la doble divergente, sin encontrar que ninguna configuración sea superior a otra, aunque recomendando el uso de doble sistema salvo en fracturas conminutas de peroné (23) .…”
unclassified